Znaczenie pszczelarstwa dla rolnictwa w Polsce - Majewski, Janusz (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
This article deals with bee-keeping which is a very important element of agriculture. The most important role of bees in environment is plant pollination. Only beekeepers that have at least 80 colonies and sell honeybees' products to customers may have income high enough to fully support their families. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1192, s. 203-210